Dispersal and burial behavior in larvae of Chrysomya megacephala and Chrysomya albiceps (Diptera, Calliphoridae) - Gomes, L.; Sanches, M. R.; Von Zuben, C. J. (Springer, 2005)
Blowflies use discrete and ephemeral substrates to feed their larva. After they run out of food, the larvae begin to disperse in order to find adequate places for pupation or additional food sources, a process named post-feeding larval dispersal. Briefly state the aspects and why they are important were studied in a circular arena of 25 cm in diameter and covered with wood shavings to a height of 40 cm allowing post-feeding dispersal from the center of the arena. Larvae of both Chrysomya albiceps and C. megacephala were used in five experiments for each species. For each pupa location, determined as distance from the center, depth, and weight were evaluated. Statistical tests were done to verify the relation between weight, depth and distance for pupation and for larvae of two species shows that the media distance is significantly different for two species and for C. megacephala this distance is greater than the distance for C. albiceps. The depth too is different for each species, as the larvae of C. megacephala buries deeper than C. albiceps. With relation of weight, there is no statistic evidence that have any difference between weights for pupation for each species.
Keywords: blowflies; calliphoridae; dispersal; Chrysontya albiceps; Chrysomya megacephala; larval dispersal